PEMETAAN KAPASITAS DUKUNG TANAH KELURAHAN LEMPUING KOTA BENGKULU - Rena Misliniyati; Makmun R. Razali (Universitas Bengkulu, 2019)
Lempuing is one area in the coastal city of Bengkulu with predominantly sandy soil consistency. This study aims to map the soil bearing capacity of sand Village Lempuing based on data sondir. To achieve these objectives, data collection sondir test at some point spread in the city of Bengkulu Lempuing. Once the data is collected sondir required, further soil bearing capacity calculations for the two types of foundation, the foundation palms (shallow foundation) and pile foundation (the foundation). Capacity analysis results show that the depth of the foundation (Df) ? 1 m, license bearing capacity (qa) for the foundation of the palm of the width (B) 0.6m generate value qa ?1,2 kg / cm2. Meanwhile, the bearing capacity of pile foundation at 6m depth ranging between 35-130 tons. Overall analysis results are displayed in the form of maps of soil bearing capacity. Distribution of value in the map shows that the farther from the coastline, the bearing capacity of the ground at the same depth becomes greater its value.